Садиби салтівської культурно-історичної спільноти на селищі Мохнач П: критерії виділення та господарський склад - Колода, В.В. (Археологія і давня історія України, 2021)
У статті проаналізовано садибне планування
селища Мохнач П часів існування тут поселення
салтівської культурно-історичної спільноти в межах другої половини VIII — середини ІХ ст. Воно
входило до складу поселенської агломерації (мікрорегіону) з центром на городищі Мохнач. Виділяються категорії житлово-господарських споруд та
спосіб їх розміщення відносно того чи іншого житла. На основі планіграфії різних комплексів та їх
групування навколо житлових споруд визначається склад та розмір садиб, що належали окремій
родині. Здійснюється спроба визначення системи
садибної забудови поселення. Farmstead planning of Mokhnach П settlement during
the time of existence of the Saltiv cultural historical
community within the second half of the 8th — mid-
9th centuries is analyzed in the paper. The settlement
was included into the residential agglomeration (microregion)
with the center in Mokhnach hillfort. Some
categories of household living buildings and ways of
their location in relation to this or other dwelling are
distinguished within the bounds of the largest excavation
site 1. Generally, 36 Saltiv sites were identified on
the mentioned area; among them there are 4 dwellings,
4 slightly deepened household buildings, 3 summer
kitchens, 4 constructions for harvest storage (1 vault,
2 cellars and 1 box room) and 21 household pits (two of
them were used to prepare clay for ceramics production).
The planography analysis of the present complexes of
the excavation site 1 allows to admit that in the south
eastern part of the settlement there were 4 farmsteads
that belonged to separate families which did their own
housekeeping. The usable area was not large (12—
18 m2). It points to the fact that a so-called «small family
» consisting of 4—6 persons owned a certain household.
Borderlines of these farmsteads do not overlap one
another — it shows that they coexisted together at the
same time. There is enough space for passage of people
or transport vehicles between the farmsteads. Structure
of household buildings is generally similar. The dwelling
was accompanied by a slightly deepened household
building, a summer kitchen, a construction for harvest
storage, and a certain amount of household pits.
At the same time, some differences are also can be
observed. In two cases (farmstead 2, 4), a small household
pit located very close to a household building has
been discovered. In the farmsted 3 no summer kitchen
was identified, and in the farmstead 1 no construction
for harvest storage was found as well. In three other
cases (farmsteads 2—4), buildings for harvest storage
differed between one another by a form, construction
and storage capacity. In the each farmstead the amount
of household pits that could coexist at the same time
did not exceed 5 units.
Thus, it can be noticed that the square of the identified
farmsteads, the characteristics of the household
buildings, amount of supportive household pits and
their location point to the quite convenient organization
of the living space and the opportunity to do housekeeping
successfully.